Complications associated with alloplastic materials in rhinoplasty and their operative management - Storck, Katharina Julia Maria; Kotz, S.; Riedel, Frank; Veit, Johannes Adrian (Facial plastic surgery, 2023)
Whereas rhinoplasty with a reduction of the dorsum and modification of the tip is a common procedure among Caucasians, augmentation of the dorsum remains a challenge in Asians. Choice of the ideal grafting material for dorsal augmentation is a matter of preference and remains under discussion. Autologous and alloplastic materials have their advantages and disadvantages. We report our experiences of the extrusion of alloplastic materials and their management. We report of 18 patients, who had rhinoplasty in the past for dorsal augmentation with alloplastic material. Augmentation rhinoplasty was performed in Asia (n = 15) and Germany (n = 3). All cases showed recurrent signs of foreign body infection and/or partial extrusion and therefore underwent revision surgery in our centers. Once all patients had been successfully treated with antibiotics, we performed a one-stage revision rhinoplasty with explantation of the alloplastic material and subsequent reconstruction with autologous rib cartilage. The nasal dorsum was augmented with either solid rib cartilage grafts, diced cartilage in fascia, or free diced cartilage in platelet-rich fibrin. All patients received pre-, peri-, and postoperative antibiotics. The outcome was screened via clinical examination, ultrasound examination pre- and postoperatively, two-dimensional/three-dimensional (3D) imaging, and magnetic resonance imaging scans. Alloplastic augmentation of the nasal dorsum runs the risk of foreign body reaction, recurrent infections, uncontrolled scarring, and unsatisfying long-term results. We have obtained a series of aesthetically and functionally satisfying results after single-stage revision surgery with autologous cartilage and demonstrate a variety of novel postoperative screening tools including 3D imaging and high-frequency ultrasound.